Videoconference Administration of the Western Aphasia Battery–Revised: Feasibility and Validity - Dekhtyar, Maria; Braun, Emily J.; Billot, Anne; Foo, Lindsey; Kiran, Swathi (American journal of speech-language pathology, 2020)
Purpose There is a rapid growth of telepractice in both clinical and research settings; however, the literature validating translation of traditional methods of assessments and interventions to valid remote videoconference administrations is limited. This is especially true in the field of speech-language pathology where assessments of language and communication can be easily conducted via remote administration. The aim of this study was to validate videoconference administration of the Western Aphasia Battery-Revised (WAB-R). Method Twenty adults with chronic aphasia completed the assessment both in person and via videoconference with the order counterbalanced across administrations. Specific modifications to select WAB-R subtests were made to accommodate interaction by computer and Internet. Results Results revealed that the two methods of administration were highly correlated and showed no difference in domain scores. Additionally, most participants endorsed being mostly or very satisfied with the videoconference administration. Conclusion These findings suggest that administration of the WAB-R in person and via videoconference may be used interchangeably in this patient population. Modifications and guidelines are provided to ensure reproducibility and access to other clinicians and scientists interested in remote administration of the WAB-R. Supplemental Material https://doi.org/10.23641/asha.11977857.